EPIGALLOCATECHIN GALLATE IMPROVES CAUDAL FIN REGENERATION IN THE STREPTOZOTOCIN-INDUCED DIABETIC ZEBRAFISH MODEL (Journal of Pharmaceutical Negative Results, 2023)
Impaired wound healing is the leading manifestation of diabetes mellitus (DM). It is mainly triggered by chronic inflammation, hyperglycemia, hypoxia, and delayed neuropeptide signaling. The rising number of DM patients exhibiting poor healing of DM wounds has, thus, given rise to the need for therapeutic intervention. Natural extracts are said to contain high anti-oxidant and anti-inflammatory properties that decrease the pathogenesis of DM. It was recorded that epigallocatechin gallate (EGCG) can improve the blood glucose level and caudal fin regeneration in the streptozotocin-induced zebrafish model. The animals were categorized into four groups. The hyperglycemic state was maintained throughout the experiment for 21 days in the test subject. After the treatment with EGCG, the test zebrafish showed a decrease in blood glucose level from 295.5±4.7 mg/dl to 99.6±4.7 mg/dl on day 21. Results showed better regeneration of amputated caudal fin in the group treated with EGCG. The percentage regeneration in the caudal fin was 60% in diabetic subjects treated with EGCG and 66% in control subjects treated with EGCG, whereas diabetic zebrafish showed only 41% regeneration on day 21. It can be concluded that EGCG has the potency to treat impaired wounds in the DM model of zebrafish.